Second (and Third) Thoughts on Adaptive Management and Thinking and Wo rking Politically - Green, Duncan (2022)
Self-Critical reflections on AM and TWP. Linking it with The Hype Cycl e - "it feels like we are heading downward to the ‘trough of disillusi onment’ form the initial peak of ‘inflated expectations’, but we will bounce back to something more sustained, that becomes a permanent feat ure of the aid landscape".